Brevibacillus laterosporus BL1, a promising probiotic, prevents obesity and modulates gut microbiota in mice fed a high-fat diet - Weng, Guangying; Huang, Jian; Ma, Xianyong; Song, Min; Yin, Yulong; Deng, Dun; Deng, Jinping (Frontiers in Nutrition, 2022)
Scope Probiotics are a potential preventive strategy for obesity. However, with discrete efficacy and limited species of probiotics, there is a demand for novel strains with excellent anti-obesity properties. This study aimed to investigate the effects of Brevibacillus laterosporus BL1 on preventing obesity in high-fat diet (HFD)-fed mice. Methods and results C57BL/6 male mice were randomly assigned to four groups (n = 10) and fed a control diet, HFD, HFD plus B. laterosporus BL1, and HFD plus supernatant of B. laterosporus BL1, respectively for 8 weeks. The results showed that prophylactic B. laterosporus BL1 treatment reduced body weight gain by 41.26% in comparison to the HFD group, and this difference was accompanied by a reduction in body fat mass and the weight of inguinal white adipose tissues and epididymal white adipose tissue (−33.39%, −39.07%, and −43.75%, respectively). Moreover, the B. laterosporus BL1-mediated improvements in lipid profile, insulin resistance, and chronic inflammation were associated with the regulation of gene expression related to lipid metabolism and enhancement of brown adipose tissue thermogenesis. Particularly, B. laterosporus BL1 intervention significantly improved HFD-induced gut flora dysbiosis, as evidenced by a reverse in the relative abundance of Bacillota and Bacteroidota, as well as an increase in the relative abundance of bacteria that produce short-chain fatty acids (SCFAs), which in turn increased SCFAs levels. Conclusion Our findings found for the first time that B. laterosporus BL1 may be a promising probiotic for prevention of obesity associated with the regulation of gut microbiota.